Lepe slikanice - Zorman, Barbara (Jezik in slovstvo, 2008)
The article presents the factors that have conditioned the relationship between film and literature in a broad sense, while in a narrower sense conditioning the selection of literature on which film is based and its filmicinterpretation in Slovenia between 1948 and 1991. The prevailing thematic categories of literature interpreted in film during this period are also highlighted.
Keywords: 1948/1991; ekranizacija; film adaptation; Slovene literature; slovenska književnost; slovenski film